The sorption of single- and multi-heavy metals in aqueous solution using enhanced nano-hydroxyapatite assisted with ultrasonic. Issue 3 (June 2021) - Zhou, Cailing; Wang, Xiyu; Wang, Yiwei; Song, Xin; Fang, Danfei; Ge, Shifu
Abstract: Nano-hydroxyapatite (nHAP) has been often used as environment material for the remediation of heavy metal contaminated water and soil. Here, an enhanced nHAP was synthesized with the assistance of ultrasonic and was employed for the sorption of single- and multi-heavy metals. The characteristics of SEM, TEM, XRD, FTIR and XPS were utilized for the investigating of competitive sorption mechanism and the metal properties were correlated with the sorption capacities. The impact of ultrasonic time on the performance of nHAPs varied from different metal ions with the apparent improvement on the uptake of Pb 2+, followed by Cu 2+ and Zn 2+, while without significant effects on for Cd 2+ . The maximum sorption capacity values of nHAP were 1352, 272, 285 and 304 mg g –1 for Pb 2+, Cu 2+, Zn 2+ and Cd 2+, respectively. Competitive sorption would seriously affect the uptake of Cd 2+ while exerting little influence on Pb 2+ for their different metal properties and dominant sorption mechanisms. The enhanced nHAP synthesized with ultrasonic simultaneously presented a high sorption capacity for several heavy metals which could be a promising environmental material for wastewater treatment and soil remediation. Graphical Abstract: ga1 Highlights: Appropriate ultrasonic benefited the nano-hydroxyapatite properties. The best sorption capacities of Pb 2+, Cu 2+, Zn 2+ and Cd 2+ are 1352, 272, 285 and 304 mg g –1 respectively. The sorption of Cd 2+ would be seriously affected in competitive sorption while Pb 2+ not. Metal properties exerted significant effect on the competitive sorption.